Study of Reactive Intermediates: 1. Transient Stannylenes in Solution; 2. Time-resolved Spectroscopic Studies of Di-tert-butylsilylene in Solution - Duffy, Ian (My University, 2018)
The transient Sn(II) compounds dimethyl-, diphenyl-, methylphenyl-, and dimesitylstannylene (SnMe2, SnPh2, SnMePh, and SnMes2, respectively) have been successfully detected and characterized in solution. The stannylenes were generated by photolysis of appropriately substituted 1-stannacyclopent-3-ene derivatives, which have each been shown to extrude the respective stannylene cleanly, through stannylene trapping studies using dichlorodimethylstannane (Me2SnCl2) as the substrate. Quantum yields for stannylene extrusion have been measured in three cases, and found to be in the range of 0.4 - 0.8. Laser flash photolysis of the stannacyclopent-3-ene derivatives in deoxygenated hexanes affords promptly-formed transient absorptions assigned to SnMe2 (λmax = 500 nm; λ500 = 1,800 ± 600 M-1cm-1), SnPh2 (λmax = 300, 505 nm; λ500 = 2,500 ± 600 M-1cm-1), SnMePh (λmax = 280, 500 nm) and SnMes2 (λmax < 270, 330(sh), 550 nm), which decay on the microsecond timescale with second order kinetics, consistent with dimerization being the major reaction in the absence of a substrate. Dimerization of SnMe2 and SnMes2 affords species exhibiting λmax = 465 nm and λmax = 490 nm, respectively, which were assigned to the expected Sn=Sn doubly-bonded dimers, tetramethyl- and tetramesityldistannene, respectively. In contrast, the spectrum of the dimer formed from SnPh2 exhibits strong absorptions in the 280 - 380 nm range and a very weak absorption at 650 nm, on the basis of which it is assigned to phenyl(triphenylstannyl)stannylene (SnPh(SnPh3)). The reaction of acetic acid (AcOH) with SnPh2 and SnMes2 proceeds via arene elimination. With SnMe2, the products are derived from the elimination of methane and O-H insertion, while SnMePh reacts to afford both benzene and methane in a ca. 3:2 molar ratio. σ-Bond insertion of SnMe2 with tributylchlorostannane (Bu3SnCl) yields the formal Sn-Cl insertion product, Bu3SnSnMe2Cl. Lewis acid-base complexation with simple aliphatic O, S, and N donors proceeds rapidly and reversibly, generating the corresponding stannylene-donor pairs, and exhibiting absorption maxima λmax ~ 310 - 385 nm. Equilibrium constants (Keq) upon O-donor coordination afford stabilization energies of -1.9 to -4.0 kcal mol-1 for SnMe2 and SnPh2, and suggesting a Lewis acidity order SiR2 > SnR2 > GeR2 (R = Me, Ph). Complexation of SnMes2 with O, S and N donors proceed with a reduction in reaction exergonicity relative to SnPh2. Reactions of SnMe2 and SnPh2 with Bu3SnH and C-C unsaturated compounds proceed with the characteristics of reversible complexation, affording short-lived Lewis acid-base products detectable by transient UV-vis spectroscopy (λmax = 375 - 430 nm). Di-tert-butylsilylene (Sit-Bu2) has also been successfully detected and characterized in solution by laser flash photolysis methods, via the photolysis of 7,7-di-tert-butyl-7-silabicyclo[4.1.0]heptane and hexa-tert-butylcyclotrisilane. This transient silylene exhibits a UV-vis absorption band centred at λmax = 515 nm and decays with second order kinetics to afford a long-lived product assigned to tetra-tert-butyldisilene (λmax = 290, 435 nm). Absolute rate constants (kQ) were determined for the reactions of Sit-Bu2 with several silylene substrates in hexanes at 25 °C. Sit-Bu2 is seen to react slower compared to SiMe2, with krel (= kQSiMe2/kQSitBu2) ranging between 0.8 - 310, cycloaddition reactions having exhibited the largest sensitivity to the tert-butyl for methyl substitution.
Keywords: Stannylene